Determination of Cutting Properties, Protein and Mineral Content of Silage Corn Stalk - Kocabiyik, Habib; Polat, Refik; Oktem, Abdullah (Asian Journal of Chemistry, 2010)
The present research determined maximum shearing force, shearing stress, shearing energy and specific shearing energy for silage corn stalks. The mechanics of shearing on rigid surfaces was investigated via cutting tests. Shearing forces were measured using a cutting experiment setup and dynamometer. The specific shearing energy was calculated by using the area under the cutting force curve versus displacement curve. The shearing properties of corn stalks were evaluated at three moisture content levels of 66.5, 53.6 and 45.8 % d.b. The shearing properties were also evaluated at four sections of the corn stalks, from the bottom to the top (0-10, 10-20, 20-30 and 30-40 cm). At the end of the research, maximum shearing force, shearing stress, total shearing energy and specific shearing energy increased from 63.36 to 97.28 N, from 93.16 to 143.38 MPa, from 216.36 to 284.93 J and from 35.18 to 57.21 J cm2, respectively in the moisture range from 66.5 to 45.8 % db. The results showed that the shearing values increased as the moisture content increased from the lower to the upper stalk sections. The protein content of silage corn stalk was 2.49 %. Macro nutrient values in the silage corn stalk such as Ca, P and S were determined as 0.346, 0.156 and 0.140 %, respectively. Micro nutrient values in the silage corn stalk such as Fe, Cu, Zn and Mn values were 10.32, 2.92, 13.12 and 16.44 mg kg-1, respectively.